PENERAPAN ASAS GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI INDONESIA BERDASARKAN UNDANG – UNDANG NOMOR 25 TAHUN 2009 - Rahmawati, Ermalena; Suardita, I Ketut (Kertha Negara : Journal Ilmu Hukum, 2014)
Poor public services by the government which is influenced by internal factorsbureaucracy could be the circumstances , either in the form of organization ( structure ,personnel placement , effectiveness of ) the effectiveness of communication between units ,resources and empowerment . Good governance as an ideal concept in the context of theimplementation of governance principles therein offered how the concept of goodgovernance is expected to realize as much as possible the implementation of thegovernment public service to the community . In analyzing this problem the authors useresearch methods with an emphasis on the normative juridical analysis of laws as primarylegal materials and other legal materials as secondary legal materials . In connection withthe enactment of Act No. 25 of 2009 as an effort to implement public service settings can besynergized with the principles of good governance for the fulfillment minimum standardsthat required in order to meet society's expectations in order to achieve optimization ofqualified and effective public services.
Keywords: Good Governance, Public Services, Welfare